The gothic tradition - Stevens, David, 1947-; Barlow, Adrian (Cambridge ; New York : Cambridge University Press, 2015)
"The Gothic Tradition is a new title in the Cambridge Contexts in Literature series. It is designed to support the needs of advanced level students of English literature. Each title in the series has the quality, content and level endorsed by the OCR examination board. However, the texts provide the background and focus suitable for any examination board at advanced level. The series explores the contextual study of texts by concentrating on key periods, topics and comparisons in literature. Each book adopts an interactive approach and provides the background for understanding the significance of literary, historical and social contexts. Students are encouraged to investigate different interpretations that may be applied to literary texts by different readers, through a variety of activities and questions, the use of study aids, such as chronologies and glossaries, and the inclusion of anthology sections to exemplify issues." http://www.loc.gov/catdir/description/cam022/2001278650.html
Approaching the Gothic tradition -- Approaching the texts -- Texts and extracts -- Critical approaches -- How to write about the Gothic
Includes bibliographical references (pages 120-125) and index
Keywords: English literature -- 19th century -- History and criticism; English literature -- 18th century -- History and criticism; Gothic revival (Literature) -- Great Britain; Gothic literature -- History and criticism; Criticism, interpretation, etc